Controlling the Chromaticity of Small-Molecule Light-Emitting Electrochemical Cells Based on TIPS-Pentacene - Weber, Michael; Adam, Matthias; Tykwinski, Rik; Costa, Ruben Dario (Advanced Functional Materials, 2015)
This work demonstrates a novel proof-of-concept to implement pentacene derivatives as emitters for the third generation of light-emitting electrochemical cells based on small-molecules (SM-LECs). Here, a straightforward procedure is shown to control the chromaticity of pentacene-based lighting devices by means of a photoinduced cycloaddition process of the 6,13-bis(triisopropylsilylethynyl) (TIPS)-pentacene that leads to the formation of anthracene-core dimeric species featuring a high-energy emission. Without using the procedure, SM-LECs featuring deep-red emission with Commission Internationale d'Eclairage (CIE) coordinates of x = 0.69/y = 0.31 and irradiance of 0.4 extgreekmW cm-2 are achieved. After a careful optimization of the cycloaddition process, warm white devices with CIE coordinates of x = 0.36/y = 0.38 and luminances of 10 cd m-2 are realized. Here, the mechanism of the device is explained as a host–guest system, in which the dimeric species acts as the high-energy band gap host and the low-energy bandgap TIPS-pentacene is the guest. To the best of the knowledge, this work shows the first warm white SM-LECs. Since this work is based on the archetypal TIPS-pentacene and the photoinduced cycloaddition process is well-knownfor any pentacenes, this proof-of-concept could open a new way to use these compounds for developing white lighting sources.
EAM Import::2019-03-13